JENIS POHON PENYUSUN DAN POLA PEKARANGAN DI DESA TIRTOADI, MLATI, SLEMAN, YOGYAKARTA - , NUNIK DAYU ASTUTI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Yard is one of the complex agroforestry systems that involve many kinds of trees. This study aims to inventory the species that make up the yard in the village of Tirtoadi, knowing the various patterns used local yard. And the results of this research can provide information about the types of trees making the most and grow well in that location so it is useful for the management of the next yard. This research was conducted in the village of Tirtoadi, Mlati Subdistrict, Sleman District, Yogyakarta Province. The method used is 100% a survey method. The samples were 9 pekaranagan are divided into three zones, namely Zone A (above), zone B (middle) and zone C (bottom). The survey results revealed that the types of trees making at Village Tirtoadi there are 35 species, consisting of 21 trees and 14 fruit-tree timber. Yard pattern used is random mixture. In the third zone the obtained results, ie zone A (above) is Hamlet Pundong altitude 212m above sea level, Making up most types melinjo tree (Gnetum gnemon). Zone B (middle) is Hamlet Ketingan altitude 201m above sea level, Most types penyususn melinjo tree (Gnetum gnemon). And zone C (bottom) height of 190 m above sea level, Making up most types of rambutan trees (Nephelium lappaceum).